OPTIMALISASI POTENSI LAHAN GUMUK PASIR UNTUK PARIWISATA DI KAWASAN PARANGTRITIS YOGYAKARTA - , Mashudi Majeri ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims at optimizing the potency of sand dune areas for tourism in the areas of Parangtritis. The main site of the study was in areas of the natural monument of barchans sand dune. The study was conducted using a descriptive qualitative method. Samples of the site was selected by a purposive sampling technique, of local people was selected by a snow-ball sampling technique, and of tourists was selected by an acccidental sampling technique. The data on the potency of sand dune areas were analyzed by the SWOT technique and based on the function of sand dune areas. The potency of sand dune areas was optimized by considering a direction of land use for tourism, land capacity, land suitability, the potency of land in accordance with the goal of sustainable land management, and the constraints of management. Based on the results of the study, it can be concluded that the optimization of the potency of sand dune areas for tourism was done by: 1) developing tourism based on a sustainable eco- and edu-tourism